The Influence of Social Media Marketing (Instagram) and Influencer Marketing on the Purchase Decision of Mie Gacoan Among Digital Business Study Program Students, State University of Medan - Panjaitan, Bon Jovi Marselino; Munthe, Salman; Fikri, Miftah El (Economic: Journal Economic and Business, 2025)
This study aims to analyze the influence of Social Media Marketing through the Instagram platform and Influencer Marketing on the purchase decisions of Mie Gacoan culinary products among students of the Digital Business Study Program at Universitas Negeri Medan. The research employed a quantitative approach with a descriptive-associative method. Data were collected through questionnaires distributed to 130 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS version 21. The results show that both Social Media Marketing (Instagram) and Influencer Marketing have a positive and significant effect, both partially and simultaneously, on purchase decisions. These findings highlight the important role of digital marketing strategies through social media and influencers in shaping consumer purchasing decisions.